CIRCULATORY SHOCK - Andrade Vicente, Walter Villela; Rodrigues, Alfredo; Silva Júnior, Jairo Rosa (Medicina (Ribeirao Preto), 2008)
Practical physiological aspects of both the cardiovascular and the circulatory system, which help to give an insight into the hemodynamic abnormalities that underlie the different symptoms of circulatory shock, are presented. Furthermore, basic therapeutic methods for the treatment of circulatory shocks are discussed.